ANALISIS DETERMINAN KEMISKINAN DI DAERAH EKS KARESIDENAN KEDU TAHUN 2016-2020 - Zulfa Khanifah; Whinarko Juliprijanto (JOEL: Journal of Educational and Language Research, 2022)
The purpose of this study is to analyze the effect of unemployment, human development index, and dependency ratio on the number of poor people in the Kedu Residency 2016-2020. This study uses a quantitative approach. In this study the data used is panel data obtained from the Central Java Statistics Agency for the 2016-2020 period. The method used is panel data regression analysis of the fixed effect model with the help of the Eviews 10 application. The results show that unemployment and dependency ratio have a positive and significant effect on the number of poor people in the Kedu Residency in 2016-2020, and the human development index has a negative effect and significant to the number of poor people in the Kedu Residency in 2016-2020.